Synthesis, characterization and antimicrobial investigation of Rh(III), Ru(III) and Ag(I) complexes with some derivatives of 3-amino-2-thioxo-2,3-dihydroquinazolin-4(1H)-ones - Guda, Ramu; Battula, Kumara Swamy; Muthadi, Srujana; Kasarla, Sarika; Palabindela, Rambabu; Korra, Rajashekar; Komuraiah, Thampu Raja; Kasula, Mamatha (European Journal of Chemistry, 2016)
The reaction of 2,3-disubstituted mercapto quinazolines with 2-hydroxy benzaldehyde (HBAMQ) (1), 2-hydroxy naphthaldehyde (HNAMQ) (2), pyridine-2-carboxaldehyde (PMAMQ) (3) and thiophen-2-carboxaldehyde (TMAMQ) (4), and with metals like Rh(III), Ru(III), and Ag(I) in the presence of piperidine resulted in the formation of their respective complexes by physicochemical methods. The newly synthesized complexes were characterized by elemental analysis, magnetic data, and spectroscopic techniques like UV-Visible, IR and 1H NMR, respectively. These compounds were also evaluated for their antimicrobial activities.